Hypertrophy of the adult pylorus - Camaño, Mario; Guerrero, Omar; Chiossoni, Martha; Castiglioni, Juan (Cirugía del Uruguay, 1971)
Two cases of pyloric hypertrophy in adults are presented accompanied by considerations on the pathology and clinical aspects of this disease.